2022
DOI: 10.1007/s42729-022-00833-9
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Spray of Biosynthesized Zinc Oxide Nanoparticles Alleviate Salinity Stress Effect on Vicia faba Plants

Abstract: Previous studies recorded positive impact of ZnO NPs on plants stressed with salinity. The current work was performed to study the effect of two different concentrations of biosynthesized ZnO NPs (50 and 100 mg L−1) on faba bean plants under salinity stress. The zinc oxide nanoparticles (ZnO NPs) were synthesized using Mentha extract, and their shape and size were characterized using X-ray diffraction and transmission electron microscope while diffuse reflectance spectra were measured using UV–Vis spectrophoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 79 publications
5
16
0
Order By: Relevance
“…(2016) have also reported increase in TFC in one of the closely related species of B. juncea , namely B. nigra seedlings treated with ZnO NPs. Comparably, the ZnO NPs treatment was shown to increase the contents of TFC in Glycyrrhiza glabra seedlings ( Oloumi et al., 2015 ), Persicaria hydropiper ( Hussain et al., 2021 ) Raphanus sativus ( Mahmoud et al., 2019 ) and Vicia faba ( Mogazy and Hanafy, 2022 ) plants. The use of nanoparticles as oxidative stress producers resulted in the production of secondary metabolites like flavonoids and phenols that function as ROS scavengers ( Javed et al., 2017 ; Vela´zquez-Gamboa et al., 2021 ; Mogazy and Hanafy, 2022 ).…”
Section: Resultsmentioning
confidence: 95%
“…(2016) have also reported increase in TFC in one of the closely related species of B. juncea , namely B. nigra seedlings treated with ZnO NPs. Comparably, the ZnO NPs treatment was shown to increase the contents of TFC in Glycyrrhiza glabra seedlings ( Oloumi et al., 2015 ), Persicaria hydropiper ( Hussain et al., 2021 ) Raphanus sativus ( Mahmoud et al., 2019 ) and Vicia faba ( Mogazy and Hanafy, 2022 ) plants. The use of nanoparticles as oxidative stress producers resulted in the production of secondary metabolites like flavonoids and phenols that function as ROS scavengers ( Javed et al., 2017 ; Vela´zquez-Gamboa et al., 2021 ; Mogazy and Hanafy, 2022 ).…”
Section: Resultsmentioning
confidence: 95%
“…Attentiveness in titanium dioxide (TiO 2 ), a metallic oxide, has been growing in current times. Titanium dioxide (Titania) is the furthermost hopeful mineral oxide that is broadly being utilized for fabrications of instruments and other applications 3 , 4 . TiO 2 is encouraging for application in the light-emitting device (LCD and LED) that operates in the short wavelength array, from blue light to ultra-violet, as well as in photovoltaic solar cells detectors thin films 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Hezaveh et al [74] recommended a value of 20 mg/L to alleviate the effect of salinity stress on the Brassica napus cultivar at the flowering stage. Recently, Mogazy et al [75] demonstrated that 50 mg/L ZnO-NPs with NaCl could enhance the growth and antioxidant activity in Vicia faba under salinity stress. Similarly, in our study, a low concentration of ZnO-NPs (50 mg/L) was used and did not exert a negative impact on O. sativa genotypes.…”
Section: Discussionmentioning
confidence: 99%